Genome Sequence of Erythromelalgia-Related Poxvirus Identifies it as an Ectromelia Virus Strain - Mendez-Rios, Jorge D.; Martens, Craig A.; Bruno, Daniel P.; Porcella, Stephen F.; Zheng, Zhi-Ming; Moss, Bernard (PLOS ONE, 2012)
Erythromelagia is a condition characterized by attacks of burning pain and inflammation in the extremeties. An epidemic form of this syndrome occurs in secondary students in rural China and a virus referred to as erythromelalgia-associated poxvirus (ERPV) was reported to have been recovered from throat swabs in 1987. Studies performed at the time suggested that ERPV belongs to the orthopoxvirus genus and has similarities with ectromelia virus, the causative agent of mousepox. We have determined the complete genome sequence of ERPV and demonstrated that it has 99.8% identity to the Naval strain of ectromelia virus and a slighly lower identity to the Moscow strain. Small DNA deletions in the Naval genome that are absent from ERPV may suggest that the sequenced strain of Naval was not the immediate progenitor of ERPV.